Comparison of Quantitative and Qualitative Characteristics of Polled Bali Cattle in Bone and Barru Regencies - Zulkharnaim, Zulkharnaim; Nasir, Muh. Satrya; Al-Gazali, Al-Gazali; Hatta, Muhammad; Rahim, Lellah; Baba, Syahdar; Hasbi, Hasbi; Baco, Sudirman (State Islamic University of Sultan Syarif Kasim Riau, 2025)
Polled Bali cattle (PBC) are Bali cattle that do not naturally have horns. This study aims to compare quantitative and qualitative characteristics of PBC found in Bone and Barru Regencies, South Sulawesi. This study was conducted from June 2024 to March 2025. The number of samples aged 12 - 24 months, for quantitative characteristics using 80 heads each in Bone (40 heads) and Barru (40 heads), with a ratio of 20 males and 20 females. The qualitative characteristics used in PBC in Bone (62 heads), and in Barru (39 heads). This study used an independent samples t-test for quantitative traits and descriptive analysis for qualitative traits. The results showed that for quantitative traits, there were significant differences in withers height and body length between males from Bone and Barru, with cattle from Bone having a larger size. However, no significant differences were found in heart girth and all morphometrics for females. For qualitative traits, there are a dominant light brown coat color, black eyelid, white ear hair, white lip edge on the edge, black mouth lash, white legs (stocking) with clear boundaries, black hoof, thick backline, small dewlap size, and polled. Although they have many similarities, there are differences in several qualitative traits such as switch of tail color, body color pattern, tail length, and rump patch color. These results provide useful information regarding the differences in body dimensions of PBC in both regions, which can be the basis for planning more effective breeding and maintenance strategies.